‘Oliva’ spoon - Murugan, Rhubhambikhei; Balamurugan, Oviyea; Kannan, Liyona; Kumar, Avaneesh Santha (Universiti Teknologi MARA, Kedah, 2023)
Usage of single use plastic spoons leads to the plastic pollution and environmental degradation due to their non-biodegradable nature. Every day millions of tons of plastic utensils end up in oceans, and this number is increasing drastically. Hence, an alternative for the plastic spoons is essential to reduce the plastic pollution. This nutritious edible spoon was made with some kitchen ingredients such as ragi and wheat flour, sesame seeds and natural flavorings without using the chemical ingredients. Different type of flavorings such as chocolate flavoring, sweet potato flavoring and beetroot flavoring were used to produce flavorful and nutritious edible spoons. Investigating the hardness of the edible spoons is essential to determine its usability in holding the food and to test the heat retention of the spoon.